Can latent fingerprint disclose the sex of the donor? A preliminary test study using GC-MS analysis of latent fingerprints - Primeau, Charlotte; Dzetkuličová, Veronika; Shepherd, Tom (Journal of forensic sciences, 2023)
While fingerprints are a highly used means of identification, not every fingerprint left behind on a potential crime scene can be used for identification purposes. In some cases, the fingerprint may be smudged, partially preserved or overlapping with other prints hence distorting the ridge pattern and may therefore be not appropriate for identification. Further, fingermark residue yields a very low abundance of genetic material for DNA analysis. In such cases, the fingermark may be used to retrieve basic donor information such as sex. The focus of this paper was to assess the possibility of differentiating between the sexes of the donor of latent fingermarks. Analytical method was GC-MS analysis of the chemical compounds of latent fingermarks using 22 male and 22 female donors. Results showed 44 identified compounds. Two alcohols, octadecanol C18 and eicosanol C20 , were found to show a difference that was statistically significant between male and female donors. There is also some evidence for the possibility of distinguishing sex of the fingermark donor based on the distribution of branched chain fatty acids, as free compounds or esterified in wax esters.
Keywords: Dermatoglyphics; dermatoglyfika; profiling; Gas Chromatography-Mass Spectrometry; fingermarks; classification; lidé; Female; chemical analysis; mužské pohlaví; mass spectrometry; Male; plynová chromatografie s hmotnostně spektrometrickou detekcí; ženské pohlaví; Humans